ANALISIS PERBANDINGAN KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KOTA MANADO DAN KOTA BITUNG (Periode 2012-2016) - Prety, .; Manossoh, Hendrik; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Local Taxes is one of the sources of Local Own Revenues (PAD) to finance regional development and operational implementation of local government, Populated will depend much on the local government due to regional autonomy. To that end Local Government must be as much as possible sources of Revenue Original Region. PAD is one of the indicators in the success of regional autonomy. The higher the PAD the higher the ability of local governments to finance their own needs. The purpose of this research is to know how big the benefit to the original income of Manado City and Bitung City during the last year that is year 2012-2016. The research method used is descriptive quantitative method. The results can be drawn back Manado City is superior in contributing from local taxes to the original income in the appeal of the city of Bitung. This is not wrong from the average contribution of total local taxes to PAD in Manado City amounted to 71.39%. Meanwhile, the PAD in Bitung City is only 42.32%.Keywords: contributions, local revenue, local taxes